Multimedia University Melaka / Abdul Azim Abdul Rahman - Abdul Rahman, Abdul Azim (Faculty of Business and Management, 2025)
This work describes an internship in the telemarketing department of Multimedia University (MMU), which provided practical experience in customer relationship management, telemarketing tactics,data management, and sales assistance in the higher education industry. The internship's main goal was to help MMU with its student recruiting and marketing initiatives while honing skills in telemarketing, customer interaction, and data management. Contributing to the university's marketing efforts, comprehending the requirements of potential students, and enhancing communication were among the main learning objectives. Making outbound calls to potential students and their families and informing them about MMU's programs, admissions, and services were among the main duties. In addition, the intern confirmed leads, kept track of leads, and made sure that follow-ups were done on time. The job also included recording interactions, generating reports to maximize advertising efforts, and managing data using Second CRM. Alignment with more general recruitment objectives was assured by working together with the marketing and admissions staff. The intern learned how to manage arguments and adapt solutions for prospective students while gaining key skills in communication, persuasion, and sales strategies. Gaining expertise in CRM software and data analysis also improved the capacity to monitor leads and assess the effectiveness of campaigns. Addressing students' problems and offering suitable solutions helped them strengthen their problem-solving abilities. To sum up, the MMU internship gave me invaluable experience in telemarketing, customer service, and sales in the higher education industry. The abilities gained during this internship will help with both professional and personal development and may be used in future sales, marketing, and customer service professions.